ChemInform Abstract: Inorganic Molybdenum Octahedral Nanosized Cluster Units, Versatile Functional Building Block for Nanoarchitectonics. Issue 19 (May 2015) - Cordier, S.; Grasset, F.; Molard, Y.; Amela‐Cortes, M.; Boukherroub, R.; Ravaine, S.; Mortier, M.; Ohashi, N.; Saito, N.; Haneda, H.
Abstract Review: 125 refs.